Supramolecular Aptamers on Graphene Oxide for Efficient Inhibition of Thrombin Activity - Lin, Ting-Xuan; Lai, Pei-Xin; Mao, Ju-Yi; Chu, Han-Wei; Unnikrishnan, Binesh; Anand, Anisha; Huang, Chih-Ching (Frontiers in Chemistry, 2019)
Graphene oxide (GO), a two dimensional material with high aspect ratio and polar functional groups, can physically adsorb single-strand DNA through ππ stacking, hydrogen bonding and hydrophobic interactions, making it became an attractive nanocarrier for nucleic acids. In this work, we demonstrate a strategy to target exosites I and II of thrombin simultaneously by using programmed hybrid-aptamers for enhanced anticoagulation efficiency and stability. The targeting ligand is denoted as Supra-TBA15/29 (supramolecular TBA15/29), containing TBA15 (a 15-base nucleotide, binding to the exosite I of thrombin), TBA29 (29-base nucleotide, binding to the exosite II of thrombin) and is designed to allow consecutive hybridization of TBA15 and TBA29 to form a network of TBAs (i.e., supra-TBA15/29). The programmed hybrid-aptamers (Supra-TBA15/29) were self-assembled on GO to further boost the anticoagulation activity. The Supra-TBA15/29GO composite was formed mainly through multivalent interaction between poly(adenine) from Supra-TBA15/29 and GO. We controlled the assembly of Supra-TBA15/29 on GO by regulating the preparation temperature and the concentration ratio of Supra-TBA15/29 to GO to optimize the distance between TBA15 and TBA29 units, aptamer density, and aptamer orientation on the GO surfaces for improving the inhibition of thrombin activity toward the formation of fibrin from fibrinogen. The dose-dependent thrombin clotting time (TCT) delay caused by Supra-TBA15/29–GO was >10 times longer than that of commercially available drugs including heparin, argatroban, hirudin, and warfarin. The in vitro cytotoxicity and hemolysis analyses revealed the high biocompatibility of Supra-TBA15/29–GO. In addition, the thromboelastography of whole-blood coagulation and rat-tail bleeding assays indicate the anticoagulation ability of Supra-TBA15/29–GO is superior to the most widely used anticoagulant (heparin). Our highly biocompatible Supra-TBA15/29–GO with strong multivalent binding affinity toward thrombin (dissociation constant (Kd) = 1.9  1011 M) shows great potential as an effective direct thrombin inhibitor for treatment of hemostatic disorders.